2019
DOI: 10.1186/s13071-019-3769-0
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of genetic divergence among populations of Aedes aegypti L. (Diptera: Culicidae) in the southeastern USA

Abstract: BackgroundThe yellow fever mosquito, Aedes aegypti is a public health concern in the USA, especially in the wake of emergent diseases such as Zika and chikungunya. Aedes aegypti populations dwindled after the invasion of Aedes albopictus in the 1980s and many populations were extirpated. However, in some areas Ae. aegypti persisted in small populations and there are reports of recent resurgences of Ae. aegypti in Florida, Louisiana, Nevada and California. We assessed the population genetic structure of Ae. aeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…This work builds on previous studies from Florida and southern California by increasing the number of individuals and sites sampled, as well as the number of genetic markers. Our work supports previous findings of minimal structure (Damal et al., 2013) and a high degree of admixture in Florida (Hopperstad et al., 2019). Unlike a previous study, we find almost no evidence of Isolation by Distance in Florida (Hopperstad et al., 2019).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This work builds on previous studies from Florida and southern California by increasing the number of individuals and sites sampled, as well as the number of genetic markers. Our work supports previous findings of minimal structure (Damal et al., 2013) and a high degree of admixture in Florida (Hopperstad et al., 2019). Unlike a previous study, we find almost no evidence of Isolation by Distance in Florida (Hopperstad et al., 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Our work supports previous findings of minimal structure (Damal et al., 2013) and a high degree of admixture in Florida (Hopperstad et al., 2019). Unlike a previous study, we find almost no evidence of Isolation by Distance in Florida (Hopperstad et al., 2019). Additionally, a geographically limited study found significant differentiation among four Florida populations (Apopka, Kissimmee, Fort Myers, and Key West) using ddRADseq (Burford Reiskind et al., 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some recent examples of Ae. aegypti microgeographic population structure in the Americas has disclosed diverse population dynamics (i.e., migration and diversity) is placed in eclectic ecogeographical regions such as boat traffic driving migration in Peruvian Amazon, (5) the substantial gene flow between geographically distant cities in Florida connected by an Interstate Highway, (7,8) and the recently multiple-source invasion of diverse populations into California, (9,10) and in several regions of Brazil. (11,12,13) In Colombia, a first study based on random amplified polymorphic DNA-polymerase chain reaction products analysis (RAPD) reported local genetic population substructure in city of Cali, which was suggested involved in differences of vector competence and insecticide resistance ratios.…”
mentioning
confidence: 99%
“…aegypti populations demography, using nuclear genetic information such as polymorphic microsatellite loci and genome-wide single nucleotide polymorphisms (SNPs) approach, unveiled lack genetic concordance between differentiation patterns observed at nuclear genetic level and East, and West African mitochondrial related populations. (4,7,10,24,25) In this sense, considering that SNPs and polymorphic microsatellite loci markers have higher genetic resolution (i.e., faster mutation rate) than mitochondrial markers, the observed mitochondrial lineage polymorphisms picture is thought occurred previous to outside Africa dis-persal, and New World populations were originated by a single source from a mitochondrial polymorphic African ancient around the 16th-century, as consequence of slave trade between Africa and Americas. (4,24) Due no comprehensive evidence for population structure of Colombian Ae.…”
mentioning
confidence: 99%